1998
DOI: 10.1021/om980001o
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of (Ether−phosphine)ruthenium(II) Complexes [(η6-C6Me6)RuH(P⌒O)][BF4] Containing Reactive Ru−O and Ru−H Bonds toward Various Small Molecules and Their Application in Ring-Opening Metathesis Polymerization

Abstract: The ruthenium(II) complexes [(η6-C6Me6)RuH(P⌒O)][BF4] (5a − c; P⌒O = η2-(O,P)-chelated ether−phosphine; a, Ph2PCH2CH2OCH3; b, Ph2PCH2C4H7O2 (C4H7O2 = 1,3-dioxanyl); c, Ph2PCH2C3H5O2 (C3H5O2 = 1,3-dioxolanyl)), each having a Ru−O and Ru−H functionality, were obtained by hydride abstraction from (η6-C6Me6)RuH2(P∼O) (4a − c, P∼O = η1-(P)-coordinated ligand) with Ph3CBF4. A facile Ru−O bond cleavage occurs when 5a − c are reacted with a variety of small molecules. Carbon monoxide, acetonitrile, tert-butyl isocyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…(© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007) (arene)H[P-O] complexes. [4] Noels et al showed that complexes of the general formula RuCl 2 (PCy 3 )(arene) can be activated by treatment with diazo compounds to form ROMP-active Grubbs-type catalysts. [5] RuCl 2 (IMes)(p-cymene) (5) (IMes = 1,3-dimesitylimidazol-2-ylidene) was first reported by Nolan et al, who showed that this complex was capable of performing ring-closing metathesis (RCM) reactions.…”
Section: Introductionmentioning
confidence: 99%
“…(© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007) (arene)H[P-O] complexes. [4] Noels et al showed that complexes of the general formula RuCl 2 (PCy 3 )(arene) can be activated by treatment with diazo compounds to form ROMP-active Grubbs-type catalysts. [5] RuCl 2 (IMes)(p-cymene) (5) (IMes = 1,3-dimesitylimidazol-2-ylidene) was first reported by Nolan et al, who showed that this complex was capable of performing ring-closing metathesis (RCM) reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The N3-C8 (6a: 1.184(5); 6b: 1.186( 5)) and N1-C1 (6a: 1.178(5); 6b: 1.173( 5)) bond lengths are however similar, and are set at the upper limit for a coordinated isocyano CN group when compared with those in the only two reported crystal structures R 2 R 1 BNCCr(CO) 5 (R 2 R 1 B = C 4 H 4 N(Et)B (NC = 1.153(4) Å), 14 ((Me 3 Si) 2 CH) 2 B (NC = 1.159(5) Å 13 ) and Ru(II) isocyanide complexes (NC ∼ 1.15-1.16 Å). [29][30][31][32] They both exhibit a partial C-N triple bond character. The isocyano carbon ruthenium distances Ru1-C1 and Ru1-C8 are shorter than the sum of the single-bond covalent radii (2.00 Å), 33 thus suggesting a partially double bond character [34][35][36][37][38][39] as a result of the metal-to-ligand π-back bonding that takes place more effectively towards the isocyanoborane trans to the cyano group and involving a deviation from linearity of the CN-B axis at the N atom.…”
Section: Resultsmentioning
confidence: 99%
“…The bond angles are also very similar. For example, the Cl(1)-Ru(1)-Cl (2) [14][15][16] In some examples the dioxolane showed fluxional behaviour though, to be dependent on the strength of the Ru-O bond as dictated by the co-ligands present at the ruthenium centre. At ambient temperature in CDCl 3 both the proton and carbon NMR spectra of 4 show several broad peaks.…”
Section: Resultsmentioning
confidence: 99%